The Illocutionary Act as a Verbal Weapon : An Analysis of Cyberbullying in Bhad Bhabie’s ‘Ms. Whitman’ - Radita Astried Rizkya; Vinjellina Batubara; Sophie Meilatifah; Trivera Hana; Dian Marisha Putri (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Here, it is examined how language is employed as a weapon on the internet by means of the illocutionary acts in Bhad Bhabie's 2023 diss track "Ms. Whitman." According to J.L. Austin's and John Searle's Speech Act Theory, the paper categorizes the lyrics of the song into the various kinds of illocutionary acts-assertives, directives, commissives, expressives, and declaratives to determine how word aggression is an instrument of cyberbullying. Through qualitative text analysis, the study reveals expressive and assertive acts most prominent in the lyrics to disseminate defamatory claims, insults, and emotional harm against the object of attack Alabama Barker. Commissive and directive acts, on the other hand, serve to threaten, command, and dominate. The analysis shows how these speech acts collectively construct a model of systematic online verbal attack under the guise of musical performance. The findings show how music culture will tend to normalize aggression, make boundaries between entertainment and harassment opaque, and place audiences' understanding of digital communication ethics. The conclusion synthesizes the recommendation of media education as a means to enable listeners to critically understand the linguistic power of such content.